2018
DOI: 10.3389/fped.2018.00270
|View full text |Cite
|
Sign up to set email alerts
|

Infants Are Exposed to Human Milk Oligosaccharides Already in utero

Abstract: Human milk oligosaccharides (HMOs) are complex carbohydrates that are highly abundant in and, in their complexity, unique to human milk. Accumulating evidence indicates that exposure to HMOs in the postnatal period affects immediate as well as long-term infant health and development. However, studies reported in the 1970s showed that HMOs already appear in maternal urine and blood during pregnancy and as early as the first trimester. In this pilot study we aimed to determine whether or not HMOs also appear in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 20 publications
0
24
0
1
Order By: Relevance
“…Another example of the microbiome and epigenetic interactions was shown by Vähämiko et al, who showed that DNA methylation was reduced in the promoters of the obesity-associated genes FTO and MC4R in women who had probiotic supplementation with Lactobacillus rhamnosus GG and Bifidobacterium lactis Bb12 and their children during pregnancy (Table 1 ) [ 36 ]. In this regard, early-life (intra-uterine) exposure to these gut microbiota and their diet-derived metabolites might influence the development of the infant’s microbiome post-partum and the long-term regulation of metabolism [ 37 ]. Future research focusing on the epigenome of pregnant women and their children and its relationship with the composition of amniotic fluid is needed.…”
Section: Gut Microbiota–derived Metabolites Epigenetics and Obesitymentioning
confidence: 99%
“…Another example of the microbiome and epigenetic interactions was shown by Vähämiko et al, who showed that DNA methylation was reduced in the promoters of the obesity-associated genes FTO and MC4R in women who had probiotic supplementation with Lactobacillus rhamnosus GG and Bifidobacterium lactis Bb12 and their children during pregnancy (Table 1 ) [ 36 ]. In this regard, early-life (intra-uterine) exposure to these gut microbiota and their diet-derived metabolites might influence the development of the infant’s microbiome post-partum and the long-term regulation of metabolism [ 37 ]. Future research focusing on the epigenome of pregnant women and their children and its relationship with the composition of amniotic fluid is needed.…”
Section: Gut Microbiota–derived Metabolites Epigenetics and Obesitymentioning
confidence: 99%
“…In the light of recent reports, newborns already have contact with free oligosaccharides during the prenatal period of their life. Last year, Wise and coworkers [169] published the first study indicating that free oligosaccharides are also present in the urine of mothers and amniotic fluid at birth, but at a lower level than in four-day colostrum. The presence of 2 -FL, 3-FL, difucosyllactose (DFL), and 6 -SL was demonstrated, but their profile differed from that for colostrum.…”
Section: Fucosylated Hmos Are Present Not Only In Human Milkmentioning
confidence: 99%
“…Acerca del significado funcional de esta presencia en el líquido amniótico solo cabe especular. La excreción urinaria de HMOs se detecta desde finales del primer trimestre del embarazo, lo que indica un pasaje por la circulación sistémica y llegando probablemente a todos los órganos maternos y al feto 30 .…”
Section: Destino De Los Oligosacáridos De La Leche Maternaunclassified